Penggunaan Ekstrak Daun Eceng Gondook (Eichornia crassipes) Sebagai Pengawet Terhadap Kualitas dan Kuantitas Telur Ayam Ras - Ismail, Siskawaty; Mandey, Jet Saartje; Tulung, Yohanis R. L. (Sam Ratulangi University, 2023)
This research was conducted for 3 months in the laboratory of the Department of Animal Husbandry, State University of Gorontalo. This study used an egg sample of 240 eggs of purebred chickens. Eggs were divided into 4 treatments, each treatment was repeated 3 times. A0 = 0% (eggs without treatment), A1 = 10% (eggs soaked at 10% level of water hyacinth leaf extract), A2 = 20% (eggs soaked at 20% level of water hyacinth leaf extract), A3 = 30% (eggs by immersing 30% level of water hyacinth leaf extract). B0 (1 day old egg), B1 (14 day old egg), B2 (21 day old egg), B3 (28 day old egg). The research was conducted by measuring egg weight, air voids, HU value, egg yolk color, and taste. Flavor. Data were analyzed using a completely randomized design (CRD), and further tests were carried out using Duncan's test. The results of this study showed that the effect of tannin content on the level of 20% water hyacinth leaf extract was able to maintain egg quality compared to eggs that were not given treatment (control). Because the tannin solution derived from water hyacinth leaves is able to cover the egg shell pores properly.